Mobility of phosphorus from organic and inorganic source materials in a sandy soil - Raphael Passaglia Azevedo; Ignacio Hernán Salcedo; Priscila Alves Lima; Vânia da Silva Fraga; Regina Maria Quintão Lana (International Journal of Recycling of Organic Waste in Agriculture)
Abstract Purpose The long-term use of manure as a source of nutrients can promote phosphorus (P) leaching, especially in sandy soils. The aim was to evaluate P mobility from organic and mineral sources in columns, linked with the Dystric Xeropsamments adsorption characteristics with long-term organic fertilization regime. Methods The mineral, chemical, and physical properties of the samples were characterized, including Langmuir adsorption and desorption kinetics. The P mobility was determined in one leaching experiment, in 20 cm soil columns. The topsoil (0–10 cm) layer was treated with organic (cattle, swine, goat, and hen manure) and inorganic fertilizers. Leaching was corresponding to 10 pore volumes (PV), 1 PV day−1. Aliquots of the leachate were collected to analyze P concentrations. After the leaching, the columns were sliced into 5-cm sections for the analysis of water-extractable P (WEP). Results The mineral source obtained higher leaching of P and between the organic sources the bovine and swine manure. The latter were the ones that had higher value of Pw in the soil after the leaching. Due to the increase of the adsorption capacity of P with depth, there was a reduction in the mobility of P, and an unbalance of Pw in the soil was found. Conclusions The mobility of P depends on the concentration of the soluble P soil or added material; moreover, the presence of Fe and Al oxides, even in small amounts, reduces the mobility of P in sandy soil.